Editorial: Cytoskeleton in the focus of anti-cancer therapy: In a search of novel biomarkers and combinatorial therapy approaches - Vorobjev I. (Frontiers Media SA, 2022)
This editorial introduces a thematic collection focused on the cytoskeleton’s role in cancer biology and treatment. It highlights recent advances in targeting cytoskeletal elements—such as microtubules and actin filaments—as therapeutic strategies against tumor progression and metastasis. Emphasis is placed on identifying novel cytoskeletal biomarkers and exploring combination therapies that leverage cytoskeletal disruption alongside immunotherapy and chemotherapy. The collection reflects growing interest in translating cytoskeletal research into precision oncology applications.
Keywords: cytoskeleton, cancer markers, anti-cancer therapy, microtubules (MT), actin, type of access: open access